2021
DOI: 10.3390/s21051585
|View full text |Cite
|
Sign up to set email alerts
|

Surface Plasmon Enhanced Fluorescence Temperature Mapping of Aluminum Nanoparticle Heated by Laser

Abstract: Partially aggregated Rhodamine 6G (R6G) dye is used as a lights-on temperature sensor to analyze the spatiotemporal heating of aluminum nanoparticles (Al NPs) embedded within a tetrafluoroethylene, hexafluoropropylene, and vinylidene fluoride (THV) fluoropolymer matrix. The embedded Al NPs were photothermally heated using an IR laser, and the fluorescent intensity of the embedded dye was monitored in real time using an optical microscope. A plasmonic grating substrate enhanced the florescence intensity of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 79 publications
(117 reference statements)
1
4
0
Order By: Relevance
“…Each particle featured a volumetric energy generation term consistent with the simulated energy absorption, which was consistent with our previous reports . Previous experiments confirmed that the grating itself generates negligible heating during irradiation . A more detailed simulation configuration and results can be seen in Figure S3.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Each particle featured a volumetric energy generation term consistent with the simulated energy absorption, which was consistent with our previous reports . Previous experiments confirmed that the grating itself generates negligible heating during irradiation . A more detailed simulation configuration and results can be seen in Figure S3.…”
Section: Resultssupporting
confidence: 87%
“…40 Previous experiments confirmed that the grating itself generates negligible heating during irradiation. 41 A more detailed simulation configuration and results can be seen in Figure S3. The nearly constant temperature ramp rate, shown in the offsets of Figure 3, is a key feature in the transient temperature profiles and results from the 7 μs (446 nm) laser rise time.…”
Section: Resultsmentioning
confidence: 99%
“…Over the past decade, numerous studies have been conducted using non-invasive 2D imaging of the temperature distribution on the micron and sub-micron levels [10][11][12][13]. The most promising non-invasive measurement techniques derive from the field of luminescence thermometry, which exploits temperature-dependent spectral changes of luminescent phosphors [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…The theoretical and experimental observation concludes that sparsely distributed Al NPs could not be ignited under flash heating [55]. Previously, we reported that single Al NP residing on the grating platform could not achieve a high enough temperature to initiate any ignition by laser-induced heating [138]. A higher temperature rise rate has also been found for larger packing densities of Al NPs clusters in that more heat per unit volume is absorbed [50].…”
Section: Comsol Simulationmentioning
confidence: 87%
“…The graphene sheets conformed well to the grating surface and Al NPs, as demonstrated by atomic force microscope (AFM, Innova Bruker) and scanning electron microscope (SEM, FEI Scios) images. Similar to our experiment setup described previously [50,138], a diode laser, focused by the optical microscope objective, supplied targeted photothermal heating.…”
Section: Graphene-isolated Aluminum Particles Reaction In Oil Mediummentioning
confidence: 99%